Sustainable farmer livelihoods and enhancement of food security in Mbhashe Municipality, Eastern Cape Province, South Africa - Bese, David Fundisile (University of the Free State, 2020)
The present study aimed to investigate how smallholder farmers use sustainable farming practices and how this contributes to their household and food security. Data were collected from 130 smallholder farmers residing in Mbhashe Municipality in the Eastern Cape, South Africa. The approach used in this study combined household survey on sustainable agricultural practices and food security in five villages in Mbhashe Municipality. A total of 62 percent of the respondents stated that they do not use artificial mineral fertilisers. Their reasons were not connected to using sustainable farming practices; however, it ranged from lack of subsidies from the government and expensive inputs. Meanwhile, 49 percent of the respondents used animal manure because it is readily available and cheaper compared to artificial fertilisers. On the other hand, 39 percent of respondents used pesticides and the remainder did not use it because of lack of finance. The results of the regression model show that five variables namely; age, education, farm size, membership in association, household size, extension visits and farmers’ perceptions were statistically significant in influencing the utilisation of Sustainable Agricultural Practices (SAPs). This implies that perceptions of farmers, education, gender, membership in an association and credit access were important factors in SAPs adoption. In terms of food security, 81 percent households were food secure in the study area. Rarely has there been situations where there is no food to eat. However, 35 percent of respondents of those who faced food shortages stated that they do so in June/July. This is the winter period were fields are usual dry, especially in the rural areas. The main cause of food shortages was mainly due to unemployment, lack of finance and weather conditions. In order to improve SAPs utilisation in South Africa, it is necessary for the government to provide incentives and provide a legal framework that will allow more organisations to provide extension services to their communities. The creation of such a framework will increase autonomy for agricultural associations to provide specialised knowledge to their areas of jurisdiction. The study proposes a model that will bring sustainability if well implemented.
Thesis (Ph.D. (Centre for Sustainable Agriculture and Rural Development)) --University of the Free State, 2020
Keywords: Agriculture; Decision Making; Food Secure; Household Economy; Sustainability; South Africa